Trifluoromethoxylation of Arenes: Synthesis of ortho‐Trifluoromethoxylated Aniline Derivatives by OCF3 Migration1. Issue 52 (30th October 2014) - Hojczyk, Katarzyna N.; Feng, Pengju; Zhan, Chengbo; Ngai, Ming‐Yu
Abstract Aryl trifluoromethoxylation by a two‐step sequence of O‐trifluoromethylation of N‐aryl‐N‐hydroxylamine derivatives and intramolecular OCF3 migration is presented. This protocol allows easy access to a wide range of synthetically useful ortho‐OCF3 aniline derivatives. In addition, it utilizes bench‐stable reagents, is operationally simple, shows high functional‐group tolerance, and is amenable to gram‐scale as well as one‐pot synthesis. A reaction mechanism of a heterolytic cleavage of the NOCF3 bond followed by recombination of the resulting nitrenium ion and trifluoromethoxide is proposed for the OCF3‐migration reaction.